PENGARUH KUALITAS PRODUK, PROMOSI, DAN KEPERCAYAAN TERHADAP MINAT BELI KONSUMEN E-COMMERCE TOKOPEDIA DI KOTA BATAM - Siregar, Sonia Hermina; Asron saputra (LPPM Universitas Putera Batam, 2022)
The development of information technology today has encouraged the birth of a neweconomic paradigm which eventually formed a virtual world in the world of commercewhich is often called e-commerce. which has been agreed upon by the seller and thebuyer. the seller must tell the price of the product purchased which determines a level ofprofit in addition. Data analysis and digital consultant, SainsOne Data, released a study onthe position and growth of the e-commerce economy in Indonesia during the first half of2018 and revealed that the 10 best online stores in Indonesia consist of e-commerce andmarketplaces. The purpose of this study was to determine the quality, promotion, andproduct trust have a simultaneous effect on the buying interest of Tokopedia e-commerceconsumers in Batam City. The method used is a quantitative method. the data sourcesused are primary data and secondary data. The data will be analyzed by descriptivemethod. The theoretical basis used is the theory of knowing that product quality,promotion, and trust have a simultaneous effect on consumer buying interest in ecommerce. by using the instrument test, reliability, classic, and multicollinearity. based onthe data analysis carried out, it was concluded that through multiple linear regressionanalysis and the results obtained that there was an influence between product quality andconsumer buying interest in the Tokpedia online store in Batam city, it could significantlyaffect the buying interest of the people of Batam city on the buying interest of online shopconsumers. Tokopedia in the city of Batam.